Anti-apoptotic effects of decyl gallate on the induction of apoptosis in A549 pneumocytes by Paracoccidioides brasiliensis gp43 - Bernardi, Thais [UNESP]; De Fátima Da Silva, Julhiany [UNESP]; Vicentin, Juliana [UNESP]; De Oliveira, Haroldo Cesar [UNESP]; Assato, Patricia Akemi [UNESP]; Marcos, Caroline Maria [UNESP]; De Paula E Silva, Ana Carolina Alves [UNESP]; Da Silva, Rosangela Aparecida Moraes [UNESP]; Regasini, Luis Octávio [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Da Silva Bolzani, Vanderlan [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; et al. (Oxford University Press (OUP), 2017)
Apoptosis is considered an escapemechanism from the host immune system for the fungus Paracoccidioides spp, and it serves as a vehicle for entry into macrophages without stimulating microbicidal activities. Recently, gp43 of P. brasiliensis was demonstrated to be involved in this process. Therefore, as a new therapeutic alternative, it is very important to study compounds that could reduce the modulation of the induction of apoptosis caused by this fungus. Decyl gallate (G14) is a known antifungal compound, and we decided to investigate its anti-apoptotic properties. Our results demonstrate that G14 was effective against apoptosis induced by gp43, as observed in epithelial cells, and led to a reduction in DNA damage, Bak down-regulation and Bcl-2 up-regulation. Together, these data show that G14 presents promising anti-apoptotic activity.
Keywords: Apoptosis; Decyl gallate; Gp43; Paracoccidioides brasiliensis